Biolinguistics Journal - (:unkn) unknown (My University, 2026)
BIOLINGUISTICS is a peer-reviewed journal exploring theoretical linguistics that takes the biological foundations of human language seriously. The Advisory Board and the Editorial Board are made up of leading scholars from all continents in the fields of theoretical linguistics, language acquisition, language change, theoretical biology, genetics, philosophy of mind, and cognitive psychology.